The regulatory role of INSIG1 in testicular Sertoli cells in boars - Shaoxuan Zhang; Hang Zhou; Simin Liu; Jing Li; Dali Wang; Boxing Sun; Hao Sun; Shuang Liang (Theriogenology, 2026)

Coupled orbital and ENSO forcing shaped the Holocene evolution of East Asian precipitation patterns - Anguo Xiao; Yanzhen Li; Teng Liu; Ze Zhang; Simin Jin; Ruiyao Zhang; Xiaosong Chen; Chunju Huang (Quaternary Science Reviews, 2026)

Low-dose sodium acetate-mediated energy compensation stabilizes oxygen-limited urea hydrolysis coupled with partial nitritation/anammox for high-strength urea wastewater treatment - Meng Yang; Yonggan Li; Yongxing Chen; Yu Zhang; Yasong Wang; Qingyu Liu; Simin Lu; Xiaojun Wang (Bioresource Technology, 2026)

Soil carbon budget regulated by straw management in a rice-based system - Lei Tang; Hanchen Wu; Simin Wang; Jianwen Zou; Shuwei Liu (Agriculture, Ecosystems & Environment, 2026)

WD repeat-containing protein 41 (WDR41) is involved in fertilization and interacts with IZUMO1 and JUNO - Wenjun Zhang; Yangyang Sun; Xu Li; Simin Liu; Huimin Su; Wanjin Xing (Theriogenology, 2026)

Willow-Leaf copper MOF networks for efficient oil-water separation and anti-microbial adhesion - Meng Xu; Simin He; Yu Wang; Lang Wei; Jinying Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Linkage-specific fucosylation patterns in human and bovine milk N-glycomes and their association with anti-inflammatory activity assessed in Caco-2 cells - Huibo Song; Bingqian Wei; Pengfei Li; Mengxue Geng; Simin Zheng; Josef Voglmeir; Guihong Zhao; Li Liu (Food Chemistry, 2026)

Molecular mechanism of perillaldehyde against Penicillium digitatum and its efficiency application by modified cornstarch in citrus preservation - Simin Jiang; Qike Liu; Meng Shi; Shenghua Ding; Rongrong Wang (Food Bioscience, 2026)

Icing distribution characteristics on wind turbine blades and their implications for anti-/de-icing element layout - Simin Li; Lixin Yang; Yiqi Liu; Haojie Zhang; Jiale Yu; Yuchen Zhou (Cold Regions Science and Technology, 2026)

Embryonic developmental toxicity and potential endocrine disruption in an estuarine benthic fish under binary and ternary exposures to organic ultraviolet absorbents - Yining Zhang; Jinzhi Ren; Luhang She; Chenyang Sun; Ziqiang Guan; Simin Xia; Jianjun Li; Jining Liu; Ying Peng (Environmental Pollution, 2026)

Astronomical and volcanic forcing of Paleocene carbon cycle perturbations in the Norwegian Sea Basin - Xiaoyue Zhang; David B. Kemp; Manuel Vieira; David W. Jolley; Simin Jin; Qing Liu; Zixin He; Xilei Sun; Chunju Huang (Global and Planetary Change, 2026)

Deep removal of aqueous arsenic by thermally activated and Fe-impregnated steel slag: Mechanism and dynamic column experiments - Shuang Chen; Simin Xiong; Zhanfang Cao; Guangyi Liu (Journal of Water Process Engineering, 2026)

Acetochlor disrupts the maternal effect of food restriction in lizards (Eremias argus): Evidence from intergenerational growth and embryonic development - Yue Zhang; Yufan Nie; Simin Yu; Yuping Liu; Hao Yang; Jiajing Sun; Dier Song; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Journal of Hazardous Materials, 2026)

Low-temperature semi-solid-state H2 battery with high energy density - Xiuquan Chen; Yuhua Zhao; Simin Hong; Xiaodong Rang; Hong Dong; Jie Zhang; Shangjun Lu; Xiang Cui; Yajing Liu (Chemical Engineering Journal, 2026)

Facile calcium-iron materials for economical removal of As(Ⅲ) and As(Ⅴ): Preparation, mechanism and granulation application - Shuang Chen; Simin Xiong; Wei Chen; Guangyi Liu (Journal of Environmental Chemical Engineering, 2026)

Gut microbiota: A critical regulator of oxaliplatin-induced peripheral neurotoxicity development - Zhen Liu; TingRong Zhang; SiMin Wang; HuaFang Yin; XiaXia Shao; LingJuan Gao; XiangDong Lu (NeuroToxicology, 2026)

Chloride source dynamics under dry–wet conditions in a watershed with imbalanced chloride input–output: Insights from tracer-aided modeling - Jianfeng Gou; Simin Qu; Wenjie Liu; Chong Wei; Xueliang Feng (Journal of Hydrology, 2026)

Lactobacillus plantarum ameliorates intrahepatic cholestasis by modulating the gut microbiota and tryptophan metabolism - Shijing Dong; Liping Guo; Chenyang Xuan; Chenhui Zhu; Zongze Han; Nian Chen; Xinyu Wang; Meng Shen; Xiaoxuan Wei; Hui Yang; Xue Zhang; Man Liu; et al. (Food Research International, 2026)

High performance portable sensor based on excellent conductive composite MXene@Ag-MEL for detection of gallic acid in foods - Xingxing Zeng; Dongnan Zhang; Simin Chen; Xiaozi Huang; Zhenxia Zhao; Xin Li; Baoyu Liu (Food Chemistry, 2026)

Effects of low-temperature vacuum frying on scallops quality and development of a machine learning-based quality prediction model - Haiyou Dong; Songyi Lin; Xiuping Dong; Bo Liu; Hongyan Wang; Simin Zhang (Food Control, 2026)

Assessment of the semipermeable membrane effect of illite and montmorillonite on dissolved thallium diffusion - Yu Liu; Simin Hu; Lezhang Wei; Dinggui Luo; Tangfu Xiao (Engineering Geology, 2026)

Targeted and sustained release of pilose antler peptide from a thermosensitive injectable hydrogel for ischemic tissue repair - Wenjian Zhao; Nannan Xue; Zhengping Ge; Yan Wu; Ali Fathi; Simin Maleknia; Farshad Oveissi; Pei Liu; Jin-Ao Duan; Yiwei Wang (Chemical Engineering Journal, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

The ultra-large-capacity silica-supported ferric oxyhydroxide material: Preparation and mechanism on arsenic removal from water - Shuang Chen; Simin Xiong; Wei Chen; Guangyi Liu (Environmental Research, 2026)

Efficacy and safety of vunakizumab between super responders and non-super responders of patients with moderate-to-severe plaque psoriasis: a post-hoc exploratory analysis of a phase III trial - Ougen Liu; Caixia Kou; Simin Yu; Huizhong Hu; Xiaoxiao Chen; Meiying Jiang; Shifeng Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Melatonin alleviates cholestatic liver injury through modulating gut microbiota and activating the NRF2/HO-1 antioxidant pathway - Shijing Dong; Jiangpeng Liu; Chenyang Xuan; Simin Zhou; Zongze Han; Chenhui Zhu; Nian Chen; Ruiyun Liu; Weirong Wang; Hongyu Chu; Xue Zhang; Hui Yang; et al. (Tissue and Cell, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Toward closed-loop remediation: A dynamic optimization approach for hydraulic conductivity estimation and pump-and-treat design - JunZe Wei; Simin Jiang; Qi Liu; Xun Zhang; Na Zheng; Jingwen Xing (Journal of Contaminant Hydrology, 2026)

Construction of a multilayer perceptron based intelligent platform for dynamic quality monitoring and shelf-life prediction of bivalves - Yi Yuan; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Jiaxin Qiang; Junbo Chu; Simin Zhang (Food Chemistry, 2026)

Structural deformation monitoring data augmentation based on modified Transformer - Simin Liu; Weiping Jiang; Ruiqi Liu; Jian Wang; Zhao Li; Zhongtao Ye (Engineering Structures, 2026)

Engineered asymmetric biomimetic skin patch with dynamic biointeractivity via microphase separation for enhanced wound regeneration - Dongmei Zhang; Simin Chen; Yihui Liu; Zixin Wang; Jiayi Wang; Shilian Zheng; Zijia Zhang; Qianjie Zhang; Wanpin Zhang (Chemical Engineering Journal, 2026)

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Phthalate exposure and hepatocellular carcinoma: Unraveling mechanisms through network toxicology - Simin Zhan; Chun Li; Kaiyi Zeng; Yanhao Ran; Chenyu Liu; Yunshuo Zhang; Zekai Zeng; Chuntian Wang; Ziqing Yang (Toxicology, 2025)

Fault diagnosis of Autonomous Underwater Vehicle thruster based on semi supervised interference suppression network - Hongchao Wang; Guoqing Xue; Bowen Liu; Jianwen Jiang; Li Yu; Simin Li; Wenliao Du (Ocean Engineering, 2025)

Hydrological and geochemical controls on CO2 and CH4 emissions from a temperate glacier-fed river on the Tibetan Plateau - Zhiheng Du; Tao Pu; Fangping Yan; Yu Zhu; Zizhen Jin; Lei Wang; Simin Xie; Changlian Tao; Shijin Wang; Shiyin Liu; Cunde Xiao (Journal of Hydrology, 2025)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Plant sterol ester-modified naringenin liposomes: A novel strategy for effectively penetrating the mucus barrier - Liuqing Yang; Jingjian Liu; Shuqi Liang; Baihui Guo; Gaodan Liu; Tarun Belwal; Simin Feng (Food Research International, 2025)

Improved water solubility of myofibrillar protein through enzymatic deamidation and glycosylation: Insights into molecular behavior of myosin - Miao Feng; Yuxin Huang; Xuefei Wang; Simin Zheng; Qian Chen; Baohua Kong; Haotian Liu; Chao Zhang (Food Chemistry, 2025)

L-theanine protects against acute alcohol-induced brain injury via cGMP/PKG signaling activation - Jiahao Yang; Xuhui Dang; Simin Tan; Jiayou Gu; Kehong Liu; Zhihua Gong; Wenjun Xiao (Food Bioscience, 2025)

Potassium and phosphorus co-doped g-C3N4 with improved carrier migration for efficient photocatalytic degradation of 2,4-dichlorophenoxyacetic acid under visible light - Shan Liu; Simin Long; Yi Zhao; Zhonglin Chen; Jimin Shen; Gang Fu; Jiaxu Zhang; Jing Kang (Environmental Research, 2025)

Insight into carbon-carbon coupling mechanism for syngas to higher alcohols over agglomeration-induced CuZn catalysts - Simin Du; Penglong Jia; Lei Sun; Chenyang Wang; Haijun Guo; Yongjun Liu; Hui Bai; Danni Xun; Maohong Fan; Wei Huang (Chemical Engineering Journal, 2025)

Study on the effects of phosphoric acid-modified biochar on the adsorption behavior and bioavailability of oxytetracycline in saline-alkali soils - Runfang Yao; Shiqi Tao; Yuyun Chen; Zengyu Liu; Simin Feng (Environmental Geochemistry and Health, 2025)

Carbon and water fluxes characteristics and differential regulation mechanisms in dryland ecosystems - Simin Zhang; Limin Duan; Lina Hao; Yongzhi Bao; Xin Tong; V.P. Singh; Tingxi Liu (Journal of Hydrology, 2025)

A comprehensive analysis of seasonal and interannual ecohydrological process dynamics in semi-arid dune and meadow ecosystems - Xia Li; Tingxi Liu; Huade Guan; Okke Batelaan; Limin Duan; Yongzhi Bao; Xin Tong; Simin Zhang; V.P. Singh (Journal of Hydrology, 2025)

Quality enhancement of batter-coated oysters via low temperature vacuum frying technique and machine learning-based prediction models for shelf life and quality dynamics - Junbo Chu; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Simin Zhang (Food Chemistry, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

Artifact of protracted zircon ages after high-temperature granulite-facies metamorphism - Shuaiqi Liu; Guibin Zhang; Simin Huang; Shuzhen Wang (Earth and Planetary Science Letters, 2025)

Mechanisms underlying the impacts of extreme temperatures on carbon and energy fluxes in dryland ecosystems - Simin Zhang; Tingxi Liu; Limin Duan; Yongzhi Bao; Lina Hao; Xin Tong; V.P. Singh (CATENA, 2025)

NPR1 modulates DNA replication in vascular endothelial cells via the transcription factor E2F2 - Fengqing Zhang; Hong Tang; Xiaocheng Mao; Simin Xiong; Yiqi Wan; Wei Yuan; Hongfei Liu (Genes & Genomics, 2025)

Comparative study of thermodynamic and material planetary boundary layer height in Beijing during the heatwaves - Lindong Dai; Yongnan Zhang; Yongjing Ma; Simin Yang; Zengshou Liu; Pengkun Ma; Yubing Pan; Zhiheng Liao; Shao Xiao; Yunjie Xia; Li Lu; Danjie Jia; et al. (Advances in Space Research, 2025)

Novel receptor-binding protein from phage PJNS004 for sensitive detection of Salmonella - Yibao Chen; Simin Yang; Qing Zhang; Ming Hu; Qianghua Lv; Xiaonan Zhao; Lulu Li; Yanbo Luo; Xiaohui Xu; Yujun Zhao; Yuqing Liu (Food Chemistry, 2025)

Development of fluorine-free superhydrophobic antibacterial and antifouling coatings: A multifunctional composite system for biomedical materials and metal protection - Meng Xu; Simin He; Yu Wang; Rongkai Li; Lang Wei; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Influence of biopolymer-based topsoil treatments on surface-subsurface hydrological processes: Implications for protection and restoration of sandy slopes - Jin Liu; Runqi Zhang; Miao Jing; Simin Yang; Zezhuo Song; Wenyue Che (CATENA, 2025)

Nutrient regulation targeting macrophage-controlled intestinal mucosal healing: A promising strategy against intestinal mucositis induced by deoxynivalenol - Simin Wu; Xinyu Fang; Jinfeng Zhao; Gang Liu; Peng Liao (Toxicon, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Human gut Bifidobacterium longum subsp. suillum is enriched in vitro by a pectic polysaccharide isolated from the flowers of Lilium lancifolium - Meixia Li; Renjie Liu; Tao Wang; Lana Duo; Guo Chen; Mengfei Mao; Yue Sun; Yun Li; Simin Cai; Wanqi Zhou; Haibiao Lai; Kan Ding (Carbohydrate Polymers, 2025)

Homoshell-heterocore multi-interface units jointly construct cellulose nanofibers based gradient structure film for low-reflection electromagnetic shielding and thermal management - Dingwen Yin; Jinbao Li; Gengmei Liu; Huijuan Xiu; Simin Wang; Yuxin Qin; Xuanchen Jiang; Feiguo Hua; Mengxia Shen; Xia Wang (Carbohydrate Polymers, 2025)

Hibernating male lizards (Eremias argus) cleverly respond to insecticide exposure and warming temperatures: survival rate and physical condition cannot coexist - Yue Zhang; Simin Yu; Yufan Nie; Yuping Liu; Zikang Wang; Ning Zhang; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2025)

Glyphosate threatens lizard adaptation to warming: Disruption to maternal effects - Simin Yu; Yue Zhang; Yufan Nie; Zikang Wang; Yuping Liu; Luyao Zhang; Rui Liu; Jinling Diao (Journal of Hazardous Materials, 2025)

All-in-one detecting dairy iodine based on single drop microextraction coupled with ratiometric fluorescence filter effect - Ruiqi Gao; Simin Ye; Xiaofang Yang; Ying Zhang; Yuanyuan Liu; Jinyi Zhang; Chengbin Zheng (Food Chemistry, 2025)

Characterization of physicochemical properties of different epigallocatechin-3-gallate nanoparticles and their effect on bioavailability - Lidan Cui; Baogui Liu; Zhihui Ling; Kehong Liu; Simin Tan; Zhihua Gong; Wenjun Xiao (Food Chemistry, 2025)

Numerical study on the stability of offshore pile-soil systems considering pore pressure response induced by extreme storms - Simin Xu; Xiaolei Liu; Cheng Zhang; Hong Zhang; Botao Xie; Xingsen Guo (Ocean Engineering, 2025)

Simple synthesis and excellent performance of the cow dung–based biodegradable liquid mulch for sustainable agriculture - Xiaohao Guo; Yuankai Zhou; Simin Li; Zhiwen Li; Wei Liu; Yalan Zhang; Hu Du; Wenrong Xiong; Qi Li; Yanyan Zhong; Tian Qin; Mengting Wu; et al. (Environmental Research, 2025)

Seasonal variation and environmental regulation mechanisms of energy fluxes and energy allocation in dune and meadow ecosystems - Simin Zhang; Tingxi Liu; Lina Hao; Limin Duan; Xin Tong; Yongzhi Bao; Yixuan Wang; Yu Gong; Wei Zhang (CATENA, 2025)

Cerebral [18F]AIF-FAPI-42-Based PET Imaging of Fibroblast Activation Protein for Non-invasive Quantification of Fibrosis After Ischemic Stroke - Peipei Tang; Yang Liu; Simin Peng; Zhikai Cai; Ganghua Tang; Zhou Zhou; Kongzhen Hu; Yuhua Zhong (Translational Stroke Research, 2025)

The Impact of Microplastics on Adsorption of Chlorophenols by River-Suspended Sediments - Shiqi Tao; Simin Feng; Yuyun Chen; Ting Duan; Zengyu Liu; Ling Li; Rongrong Yun; Chayma Chilouch (Environmental Management, 2025)

Water-stabilized perovskite CsPbBr3/CsPb2Br5 for high-sensitivity fluorescence “on-off-on” recognition and cell imaging - Simin He; Rongkai Li; Meng Xu; Yu Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Electromagnetic bilayer composite film: Cocoa-tree-like FL and spiky-ball-like CN structures for superior electromagnetic shielding, thermal management, and strain sensing performance - Gengmei Liu; Jinbao Li; Dingwen Yin; Huijuan Xiu; Simin Wang; Xuanchen Jiang; Yuxin Qin; Feiguo Hua; Yufei Jia; Mengxia Shen (Chemical Engineering Journal, 2025)

Selective recovery of rare earth elements from mine wastewater using the magnetic zeolite prepared by rare earth tailings - Jianhui Zhang; Jianchen Cheng; Guizhou Xu; Xuechao Hou; Zhifei Yu; Wei Liu; Yalan Zhang; Jianxin Chen; Jiahao Yang; Mengting Wu; Wanqing Yang; Simin Li; et al. (Chemical Engineering Journal, 2025)

Beneficial reuse of pyrolytic post-remediation soil to activate persulfate oxidation and avoid exposure of environmentally persistent free radicals - Mingxin Wang; Simin Song; Wei Liu; Zhenzhen Yu (Process Safety and Environmental Protection, 2025)

Arsenic removal by thermally activated limonite: Adsorption performance and mechanism - Simin Xiong; Shuang Chen; Wei Chen; Wenbin Xia; Guangyi Liu (Journal of Water Process Engineering, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Iron‐Driven Fast Decomposition of Soil Carbon Under Periodic Anoxia - Ting Liu; Xin Wang; Simin Wang; Erxiong Zhu; Steven J. Hall; Xiaojuan Feng (Global Change Biology, 2025)
Soil organic carbon (SOC) decomposition underpins soil‐atmosphere carbon exchange and is regulated by climate change‐mediated variations in soil redox conditions. Periodic anoxia, commonly occurring following precipitation, soil flooding, and erosion events, is assumed to preserve SOC. Yet, water saturation may also increase SOC decomposition relative to unsaturated conditions, and contradictory findings among previous studies remain unexplained. Here, using incubation experiments on 20 soils collected across a 24° latitude gradient in China, we show that 70% of the soils showed a higher or similar anoxic decomposition rate of SOC compared to the oxic treatment, indicating fast SOC loss under relatively short anoxia. Methane production was far lower than CO 2 due to the presence of alternative terminal electron acceptors (TEAs). Variation in alternative TEAs and microbial community shows that fast anoxic decomposition was primarily driven by iron (Fe) reduction, which accounted for up to 90% of anoxic CO 2 production. Meanwhile, positive relationships among water‐extractable organic carbon (OC), hydrochloric acid‐extractable ferrous Fe, relative abundance of Fe‐reducing prokaryotes, and the SOC decomposition rate suggest the release of readily metabolized substrates following Fe reduction. This release provided substrates for anoxic metabolism and potentially led to the loss of OC protected by Fe (Fe‐bound OC; a slow‐cycling OC pool under oxic conditions). Mass balance calculation confirms that Fe‐bound OC loss was mostly similar to elevated anoxic SOC decomposition in magnitude, and random forest modeling indicates that soils rich in reducible Fe, SOC, and Fe‐reducing prokaryotes most likely experience elevated SOC decomposition under periodic anoxia. Overall, our findings demonstrate that fast anoxic decomposition of SOC is a potentially important pathway that may stimulate SOC loss under climate change‐mediated intense hydrologic regimes, particularly for soils rich in reducible Fe and SOC.

Melatonin protects bovine oocyte from βHB-induced oxidative stress through the Nrf2 pathway - Kaiyan Zhang; Jing Guo; Simin Wang; Changguo Min; Jun Wang; Hongyu Liu; Yi Fang; He Ding; Jing Zhao; Xin Ma; Wenfa Lu (Theriogenology, 2025)

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Efficient conversion of corn straw to feed protein through solid-state fermentation using a thermophilic microbial consortium - Simin Wang; Zhi Wang; Nan Wang; Shilei Wang; Shan Zeng; Zhengzhong Xu; Dong Liu; Xiaoling Zhao; Fan Liu; Jingliang Xu; Yafan Cai; Hanjie Ying (Waste Management, 2025)

Remediation of thallium-contaminated groundwater using magnetic illite–biochar: Structural characteristics, performance and mechanisms - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2025)

Impacts of changes in climate extremes on maize yields over Mainland China - Simin Deng; Xuezhi Tan; Bingjun Liu (Food Security, 2025)

Cardiovascular disease, bone fracture, and all-cause mortality risks among postmenopausal women by arthritis and veteran status: A multistate Markov transition analysis - Hind A. Beydoun; May A. Beydoun; Jordan Weiss; Robert Brunner; Nishant K. Mishra; Ming Ding; Jean Wactawski-Wende; Philippe Jean-Luc Gradidge; Simin Liu; Jack Tsai (GeroScience, 2025)

Effects of acetochlor on the interaction between Scenedesmus and Microcystis: Integrated perspectives on toxicity, biotransformation, and competition strategies - Zikang Wang; Simin Yu; Yufan Nie; Yue Zhang; Yuping Liu; Shanshan Li; Wensheng Xiang; Jinling Diao (Journal of Hazardous Materials, 2025)

Insight into aroma dynamic changes during the whole manufacturing process of smoked Lapsang Souchong tea - Weiying Su; Zhibin Liu; Simin Huang; Daoliang Wang; Xiaoxiao Feng; Yuan Liu; Li Ni (Food Chemistry, 2025)

Versatile benzthienocarbazole isomer derivatives as efficient TADF emitters and hosts for blue multi-resonance TADF emitters - Deli Li; Jiaji Yang; Simin Jiang; Haoxiang Yuan; Denghui Liu; Zhihai Yang; Guo-Xi Yang; Mengke Li; Xuchuan Jiang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Interactive effects of aridity and local environmental factors on the functional trait composition and diversity of macroinvertebrate assemblages in dryland rivers - Jun Wang; Simin Bao; Jani Heino; Zhenyuan Liu; Peng Xie; Xuefei Zhong; Qiong Zhou (Science of The Total Environment, 2024)

Role of methanogenesis and methanotrophy in CH4 fluxes from rice paddies under elevated CO2 concentration and elevated temperature - Yuanyuan Wang; Zhenghua Hu; Botao Gu; Jingjing Xing; Chao Liu; Tingwu Liu; Simin Zhao; Xinyu Zhang; Luoyan Zhu; Ziqi Xu (Science of The Total Environment, 2024)

Energy-Adjusted Dietary Inflammatory Index and Diabetes Risk in Postmenopausal Hispanic Women - Monica D. Zuercher; Danielle J. Harvey; Lauren E. Au; Aladdin H. Shadyab; Margarita Santiago-Torres; Simin Liu; Nitin Shivappa; James R. Hébert; John A. Robbins; Lorena Garcia (Journal of the Academy of Nutrition and Dietetics, 2024)

Using a rough-fuzzy DANP technique for analysis of the key factors affecting the development of a green business in the machinery manufacturing sector - Qigan Shao; Huai-Wei Lo; Simin Liu; Changchang Jiang; Peiyao Su (Journal of Cleaner Production, 2024)

Beneficial utilization of ball-milled carbon sand to activate peroxymonosulfate oxidation: Quantitation of ROS using probe-based kinetic models and mechanism insights - Simin Song; Wei Liu; Mingxin Wang; Jinjuan Xue; Meng Yao (Journal of Environmental Management, 2024)

Simultaneously enhancing the EMI shielding performances and mechanical properties of structure–function integrated CF/PEEK composites via chopped ultra-thin carbon fiber tapes and interfacial engineering with MXene - Simin Zhang; Jinze Cui; Xingwen Kuang; Mingbin Lai; Yutai Luo; Feng Bao; Jiali Yu; Caizhen Zhu; Jian Xu; Huichao Liu (Chemical Engineering Journal, 2024)

Estimation of pollution sources and hydraulic conductivity field in a coastal aquifer under tidal effects - Chao Wu; Simin Jiang; Xuemin Xia; Yue Sun; Zhi Li; Mengdie Ju; Si Li; Shihui Liu (Marine Georesources & Geotechnology, 2024)

Characteristics of methane and carbon dioxide in ice caves at a high-mountain glacier of China - Zhiheng Du; Hao Cui; Lei Wang; Fangping Yan; Yushuo Liu; Qian Xu; Simin Xie; Tingfeng Dou; Yanzhao Li; Pengfei Liu; Xiang Qin; Cunde Xiao (Science of The Total Environment, 2024)

Associations of occupational exposure to micro-LiNiCoMnO2 particles with systemic inflammation and cardiac dysfunction in cathode material production for lithium batteries - Yaotang Deng; Guoliang Li; Lijie Xie; Xiaoliang Li; Youyi Wu; Jiewei Zheng; Simin Xian; Jiazhen Zhou; Jiabin Chen; Yuewei Liu; Qiaoyuan Yang; Qing Wang; et al. (Environmental Pollution, 2024)

Constructing multi-dimensional alternating layer nested structure for enhancing electromagnetic shielding, thermal management and strain sensing - Dingwen Yin; Jinbao Li; Simin Wang; Huijuan Xiu; Gengmei Liu; Shaoyan Huang; Sha Fan; Mengxia Shen; Yanfei Pan (Chemical Engineering Journal, 2024)

Inorganic salts released from polypyrrole nanocapsules on compact TiO2 layer for highly efficient inorganic CsPbI3-type perovskite solar cells - Dan Li; Xin Li; Kang Wang; Simin Ma; Xin Shao; Tingting Yang; Yunhui Han; Zhengguo Zhang; Shengzhong Liu; Shengwei Guo (Chemical Engineering Journal, 2024)

Fully analytical method for probabilistic stability analysis of the rainfall-induced landslide considering variability of saturated hydraulic conductivity and rainfall uncertainty - Xiaoyang Wei; Yibiao Liu; Weizhong Ren; Simin Cai; Wenhui Xu (Bulletin of Engineering Geology and the Environment, 2024)

A DNA walker based on hairpin-shaped DNA aligner and fueled by nicking endonuclease for sensitive and rapid miRNA analysis - Ting Huang; Zhenbang Lu; Peixian Mo; Piao Liu; Simin Liu; Jing Peng; Rongtian Li; Nuan Jia; Minmin Li; Zong Dai; Jun Chen; Jinxiang Chen (Analytica Chimica Acta, 2024)

A sustainable and efficient strategy for bioconverting naringin to L-rhamnose, 2R-naringenin, and kaempferol - Mengfan Lu; Simin Liu; Jiamei Liu; Linguo Zhao; Jianjun Pei (Food Chemistry, 2024)

Identification and validation of two major QTL for grain number per spike on chromosomes 2B and 2D in bread wheat (Triticum aestivum L.) - Simin Liao; Zhibin Xu; Xiaoli Fan; Qiang Zhou; Xiaofeng Liu; Cheng Jiang; Fang Ma; Yanlin Wang; Tao Wang; Bo Feng (Theoretical and Applied Genetics, 2024)

Porcine kobuvirus enhances porcine epidemic diarrhea virus pathogenicity and alters the number of intestinal lymphocytes in piglets - Simin Wu; Fang Gou; Jie Meng; Xin Jin; Wanchen Liu; Weishuai Ding; Weihang Xu; Changqin Gu; Xueying Hu; Guofu Cheng; Pan Tao; Wanpo Zhang (Veterinary Microbiology, 2024)

Spectroscopic method to study the effect of lightning return stroke channel expansion on atmospheric pressure - Jin Qin; Simin Xue; Ping Yuan; Zijiang Liu; Hua Yuan Shi; Tingting An; Hong Deng; Yingying An (Atmospheric Research, 2024)

Numerical Investigation into the Stability of Offshore Wind Power Piles Subjected to Lateral Loads in Extreme Environments - Miaojun Sun; Zhigang Shan; Wei Wang; Simin Xu; Xiaolei Liu; Hong Zhang; Xingsen Guo (Journal of Marine Science and Engineering, 2024)
Monopile foundations are extensively utilized in the rapidly expanding offshore wind power industry, and the stability of these foundations has become a crucial factor for ensuring the safety of offshore wind power projects. Such foundations are subjected to a myriad of complex environmental loads during their operational lifespan. Whilst current research predominantly concentrates on the effects of wind, wave, and current loads on monopile stability in extreme environments, it is imperative to consider the potential influence of unexpected submarine landslide loads. In this study, we provide a comprehensive overview of wind, wave, current, and submarine landslide loads on monopile foundations in extreme environments. Subsequently, we establish a finite element model for analyzing the stability of monopiles under complex lateral loads, and validate the accuracy of the model by comparing it with the previous numerical findings. A case study is performed with reference to the Xiangshui Wind Farm project to analyze the effects of varying submarine landslide densities, velocities, impact heights, and seabed sediment strengths on pile head horizontal displacement, pile rotation at the mudline, and maximum bending moment. The findings indicate that the increase in submarine landslide density, velocity, and impact height leads to an increase in horizontal displacement at the pile head, pile rotation at the mudline, and maximum bending moments, and a horizontal failure mode is observed in seabed sediments. Furthermore, under the same load conditions, a decrease in seabed sediment strength and internal friction angle triggers instability in monopiles, with a noteworthy transition from horizontal failure to deep-seated seabed sediment failure. Finally, we propose a criterion for monopile instability under diverse loading conditions.

Potential retention of dissolved organic matter by soil minerals during wetland water-table fluctuations - Simin Wang; Ting Liu; Erxiong Zhu; Chen He; Quan Shi; Xiaojuan Feng (Water Research, 2024)

Recent advances in clay minerals for groundwater pollution control and remediation - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Environmental Science and Pollution Research, 2024)

Characterization and drivers of water and carbon fluxes dynamics in dune ecosystems of the Horqin Sandy Land - Simin Zhang; Tingxi Liu; Limin Duan; Lina Hao; Xin Tong; Tianyu Jia; Xia Li; Shuo Lun (Science of The Total Environment, 2024)

On the development and recovery of soil moisture deficit drought events - Simin Deng; Xuezhi Tan; Xuejin Tan; Xinxin Wu; Zeqin Huang; Yaxin Liu; Bingjun Liu (Journal of Hydrology, 2024)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Effect of acetochlor on the symbiotic relationship between microalgae and bacteria - Zikang Wang; Simin Yu; Yufan Nie; Ran Liu; Wentao Zhu; Zhiqiang Zhou; Yongqiang Ma; Jinling Diao (Journal of Hazardous Materials, 2024)

Pilot study on ceramic flat membrane bioreactor in treatment of coal chemical wastewater - Jingxin Shi; Yarui Wang; Simin Lu; Jiahui Wang; Jingchun Liu (Chemosphere, 2024)

Nano-selenium repaired the damage caused by fungicides on strawberry flavor quality and antioxidant capacity by regulating ABA biosynthesis and ripening-related transcription factors - Yuping Liu; Rui Liu; Feifei Li; Simin Yu; Yufan Nie; Jia-Qi Li; Canping Pan; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Pesticide Biochemistry and Physiology, 2024)

Alleviative effects of mannosylerythritol lipid-A on the deterioration of internal structure and quality in frozen dough and corresponding steamed bread - Siyu Liu; Simin Gu; Ying Shi; Qihe Chen (Food Chemistry, 2024)

Golgi-triggered radiation sensitizer retention enhances the efferocytosis and immunotherapy in breast cancer with skeleton metastases - Yi-chuan Pang; Xiaotong Qiu; Simin Liu; Yanlei Huo; Xiaoli Yang; Chao Ma; Min qi; Xiaojun Chen; Zhi-hang Zhou; Zhongwei Lv (Chemical Engineering Journal, 2024)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Sustainable and efficient extraction of lignin from wood meal using a deep eutectic system and adsorption of neutral red dye with the extraction residue - Simin Wang; Min Liu; Wuxia Ge; Can Jin; Wentao Bi (Journal of Cleaner Production, 2023)

Pretreatment of Luzhou distiller’s grains for feed protein production using crude enzymes produced by a synthetic microbial consortium - Jixiang Liu; Shilei Wang; Zhi Wang; Caihong Shen; Dong Liu; Xiaojuan Shen; Longfei Weng; Yun He; Simin Wang; Jiaxin Wang; Wei Zhuang; Yafan Cai; et al. (Bioresource Technology, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

Comparison of transit time models for exploring seasonal variation of preferential flow in a Moso bamboo watershed - Jianfeng Gou; Simin Qu; Peng Shi; Huade Guan; Hai Yang; Zhicai Zhang; Jintao Liu; Zhiguo Su (Journal of Hydrology, 2023)

Hydrogeochemical evolution of groundwater impacted by acid mine drainage (AMD) from polymetallic mining areas (South China) - Yu Liu; Xianming Xie; Song Wang; Simin Hu; Lezhang Wei; Qihang Wu; Dinggui Luo; Tangfu Xiao (Journal of Contaminant Hydrology, 2023)

A multiple-methods approach to investigate dietary differences among nominally herbivorous fishes - Xianzhi Lin; Simin Hu; Yanyan Zhou; Hui Huang; Li Zhang; Sheng Liu (Marine Biology, 2023)

Occurrence and removal rate of typical pharmaceuticals and personal care products (PPCPs) in an urban wastewater treatment plant in Beijing, China - Jia Liu; Simin Ge; Peng Shao; Jianfeng Wang; Yanju Liu; Wei Wei; Can He; Lilan Zhang (Chemosphere, 2023)

Enhanced microbial contribution to mineral-associated organic carbon accrual in drained wetlands: Beyond direct lignin-iron interactions - Chengzhu Liu; Simin Wang; Yunpeng Zhao; Ya Wang; Yiyun Wang; Erxiong Zhu; Juan Jia; Zongguang Liu; Jin-Sheng He; Xiaojuan Feng (Soil Biology and Biochemistry, 2023)

Tracing global N2O emission mitigation strategies through trade networks - Kemeng Liu; Rong Ma; Kejia Yan; Bo Zhang; Simin Xu; Cuiyang Feng (Journal of Environmental Management, 2023)

Assessing efficiency of fine-mapping obesity-associated variants through leveraging ancestry architecture and functional annotation using PAGE and UKBB cohorts - Mohammad Yaser Anwar; Mariaelisa Graff; Heather M. Highland; Roelof Smit; Zhe Wang; Victoria L. Buchanan; Kristin L. Young; Eimear E. Kenny; Lindsay Fernandez-Rhodes; Simin Liu; Themistocles Assimes; David O. Garcia; et al. (Human Genetics, 2023)

Classification of Hailstone Trajectories in a Hail Cloud over a Semi-Arid Region in China - Xiaoli Liu; Kerui Min; Jianren Sang; Simin Ma (Advances in Atmospheric Sciences, 2023)

RETRACTED ARTICLE: Micromechanical behavior of jointed rock masses under uniaxial compression loading: a numerical study based on the discrete element method - Wenhui Xu; Weizhong Ren; Yibiao Liu; Chenchen Liu; Simin Cai (European Journal of Environmental and Civil Engineering, 2023)

Molecular quantification of copepod Acartia erythraea feeding on different algae preys - Simin Hu; Tao Li; Hui Huang; Sheng Liu (Acta Oceanologica Sinica, 2023)

Global trade networks bring targeted opportunity for energy-related CH4 emission mitigation - Simin Xu; Xiaofang Wu; Kejia Yan; Ying Liu; Bo Zhang (Environmental Science and Pollution Research, 2023)

Hydrogeochemistry of groundwater surrounding a pyrite mine in southern China: Assessment of the diffusive gradients in thin films technique for in situ monitoring - Yu Liu; Lezhang Wei; Hongmei Deng; Simin Hu; Xianming Xie; Dinggui Luo; Tangfu Xiao (Journal of Hydrology, 2023)

Multi-perspective synergistic construction of dual-functional heterostructures for high-temperature Li-S batteries - Yiding Li; Qiang Zhang; Simin Shen; Siqi Wang; Liangliang Shi; Dequan Liu; Yujun Fu; Deyan He (Chemical Engineering Journal, 2023)

Identification of contaminant source and hydraulic conductivity field based on an ILUES-SOM surrogate model - Na Zheng; Jinbing Liu; Xuemin Xia; Simin Gu; Yanhao Wu; Xianwen Li; Simin Jiang (Stochastic Environmental Research and Risk Assessment, 2023)

Enhancing the Thermotolerance of Isochrysis zhangjiangensis Through Co-culturing With Algoriphagus marincola - Simin Xu; Jiayi Cao; Minnan Wu; Yijun Xu; Yuanyuan Wu; Kaixi Shang; Bin Ma; Lin Zhang; Deshui Chen; Xinyu Liu; Xiaojun Yan; Jilin Xu (Marine Biotechnology, 2023)

The combined effects of atrazine and warming on environmental adaptability in lizards (Eremias argus) from the perspective of a life-history traits trade-off: Gender differences in trade-off strategies may reverse mortality risk - Yufan Nie; Zikang Wang; Simin Yu; Luyao Zhang; Rui Liu; Yuping Liu; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2023)

Comparision of nitrogen removal characteristic and microbial community in freshwater and marine recirculating aquaculture systems - Wenqian Zhang; Bo Liu; Zhenzhu Sun; Tingyu Wang; Simin Tan; Xin Fan; Danyang Zou; Yutong Zhuang; Xinting Liu; Yizhu Wang; Yanyu Li; Kangsen Mai; et al. (Science of The Total Environment, 2023)

Urinary levels of 30 metal/metalloids in the Brazilian southeast population: Findings from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Fernando Barbosa; Paula Picoli Devoz; Marcos Rafael Nogueira Cavalcante; Matheus Gallimberti; Jonas Carneiro Cruz; José Luis Domingo; Eduardo J. Simões; Paulo Lotufo; Simin Liu; Isabela Bensenor (Environmental Research, 2023)

Plasma Metabolic Analysis Reveals the Dysregulation of Short-Chain Fatty Acid Metabolism in Parkinson’s Disease - Ao Qi; Lulu Liu; Junjie Zhang; Simei Chen; Simin Xu; Yusen Chen; Lijiang Zhang; Chun Cai (Molecular Neurobiology, 2023)

Responses of macroinvertebrate functional trait structure to river damming: From within-river to basin-scale patterns - Jun Wang; Simin Bao; Kai Zhang; Jani Heino; Xiaoming Jiang; Zhenyuan Liu; Juan Tao (Environmental Research, 2023)

The effects of pollution by multiple metals derived from long-term smelting activities on soil mite communities in arable soils under different land use types in East China - Manping Liu; Zhu Li; Simin Li; Fang Liang; Chengwang Huang; Hui Pan; Jie Wu; Siyao Liu; Limin Pu; Peter Christie; Jing Song; Paul Henning Krogh; et al. (Environmental Science and Pollution Research, 2023)

Seasonal variation of transit time distribution and associated hydrological processes in a Moso bamboo watershed under the East Asian monsoon climate - Jianfeng Gou; Simin Qu; Huade Guan; Peng Shi; Zhicai Zhang; Hai Yang; Jintao Liu; Zhiguo Su; Xiaole Han (Journal of Hydrology, 2023)

Deep eutectic solvent on extraction of flavonoid glycosides from Dendrobium officinale and rapid identification with UPLC-triple-TOF/MS - Minghui Sui; Simin Feng; Gaodan Liu; Bilian Chen; Zhenhao Li; Ping Shao (Food Chemistry, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Custom-design of triblock protein as versatile antibacterial and biocompatible coating - Xiang Lan; Hao Zhang; Haishan Qi; Simin Liu; Xiangyu Zhang; Lei Zhang (Chemical Engineering Journal, 2023)

Progressively thawed soil layers differed in microbial properties and CO2 emission rates - Yaxian Hu; Xianwen Li; Huimin Liu; Xinhao Yuan; Simin Jiang; Xiaorong Wei (CATENA, 2023)

Short-term responses of phytoplankton size-fractionated structure and photosynthetic physiology to thermal effluent in a subtropical coastal bay - Simin Hu; Chen Zhang; Qingxia Liu; Tao Li; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2023)
Elevated water temperature caused by the thermal discharge from power plants can exert multiple ecological impacts on the phytoplankton community in coastal ecosystems. Most recent studies have focused on the reshaping effects on the community structure; however, the short-term response of phytoplankton physiology to thermal discharge remains unclear. This study conducted research on the scope of thermal discharge from the nuclear power plant and the size-fractionated phytoplankton structure combined with photosynthetic physiology in Daya Bay, China. The thermal discharge significantly affected the surface temperature in the outlet regions, and the thermal plume mainly diffused along the northeast coast of the outfall site, resulting in a significant difference in the surface temperature between the inlet and outlet transects ( p< 0.05). Elevated surface temperatures decreased the total chlorophyll a concentrations by 33.19% at the outlet regions, with pico-phytoplankton decreasing the most. Chlorophyll a concentrations were higher at sites further away from the outlets, indicating that elevated water temperature might stimulate the rapid growth of phytoplankton, especially nano-phytoplankton which replaced pico-phytoplankton as the dominant group at stations away from the outlets. Significant negative correlations were observed between the photochemical quantum yield ( F v /F m ) and temperature ( p< 0.05), and the relative electron transport rate (rETR) and temperature ( p< 0.05). Phytoplankton showed a normal photosynthetic physiological state at most sites with a surface temperature<33°C but was severely affected at the outlet site with a 5°C rise, decreasing from ~0.5 on the inlet transect to 0.07. During the diurnal survey, the high temperatures near the outlet at midday had a compensatory effect on phytoplankton’s light suppression. The results indicated that the physiological state of phytoplankton was clearly influenced by the thermal discharge with diurnal variation, and different size-fractionated phytoplankton groups exhibited heterogeneous responses. The findings may provide further insights into the ecological impacts of thermal discharges as well as global warming in subtropical regions.

Plant polysaccharide itself as hydrogen bond donor in a deep eutectic system-based mechanochemical extraction method - Min Liu; Simin Wang; Wentao Bi; David Da Yong Chen (Food Chemistry, 2023)

Genetic Diversity and Differences among Three F1 Families and Two Wild Populations of Genus Scylla Using Microsatellite Markers - Weifeng Gao; Wenxiao Cui; Fangchun Wu; Huiying Chen; Simin Liu; Mengyun Guan; Hafiz Sohaib Ahmed Saqib; Shaopan Ye; Mhd Ikhwanuddin; Hongyu Ma (Fishes, 2022)
Genetic diversity is the determinant of the allocation of germplasm resources in the genetic improvement of aquaculture species. In this study, three F1 families, including a hybrid Scylla family (S. paramamosain ♂ × S. serrata ♀), a paternal family of S. paramamosain, a maternal family of S. serrata, and two wild populations, including a paternal population of S. paramamosain and a maternal population of S. serrata, were used to investigate the genetic diversity and genetic difference. The results indicated that 98 alleles of nine microsatellites loci were observed in five Scylla populations. The highest average value of Ho (observed heterozygosity), He (expected heterozygosity), and PIC (polymorphic information content) of the wild S. paramamosain population were 0.790, 0.799, and 0.771, respectively, suggesting the wild paternal population has high genetic diversity. The comparative analysis of PIC, Fst (fixation index), and HWE (Hardy–Weinberg equilibrium) indicated that the paternal S. paramamosain may be more suitable for artificial breeding than the maternal S. serrata from the perspective of allele frequency. Analysis of molecular variance analysis (AMOVA) showed that the total genetic variation mainly occurred within populations (73.28%), demonstrating that artificial breeding may induce genetic differentiation of the family groups of Scylla. The results of the analysis of Fst value, UPGMA (unweighted pair-group mean analysis) dendrogram, and genetic diversity indicated that the F1 hybrid offspring had a close genetic distance and high genetic identity with the paternal S. paramamosain populations. It indicated that the F1 hybrid offspring showed potential paternal genetic affinities and a similar potential for artificial breeding with S. paramamosain. The study will provide valuable information to evaluate the difference in the genetic diversity and population structure between hybrid offspring and distinct parental populations of Scylla.

Engineering synthetic microbial consortium for cadaverine biosynthesis from glycerol - Simin Liu; Jiali Mi; Kejing Song; Haishan Qi; Lei Zhang (Biotechnology Letters, 2022)

Microbial communities associated with epilithic algal matrix with different morphological characters in Luhuitou fringing reef - Tiancheng Zhou; Simin Hu; Nan Jia; Chen Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2022)
The microbiota is an important component of the epilithic algal matrix (EAM) and plays a central role in the biogeochemical cycling of important nutrients in coral reef ecosystems. Insufficient studies on EAM microbiota diversity have led to a limited understanding of the ecological functions of EAMs in different states. To explore the microbial community of EAMs in the Luhuitou fringing reef in Sanya, China, which has undergone the incessant expansion and domination of algae over the past several decades, investigations were conducted in the reef’s intertidal zone. Five types of substrate habitats (dead branching coral, dead massive coral, dead flat coral, granite block, and concrete block) were selected, and their microbial communities were analyzed by high-throughput sequencing of EAM holobionts using the 16S rDNA V4 region. Proteobacteria was the most abundant group, accounting for more than 70% of reads of the microbial composition across all sites, followed by Cyanobacteria (15.89%) and Bacteroidetes (5.93%), respectively. Cluster analysis divided all microbial communities into three groups, namely short, medium, and long EAMs. Algal length was the most important morphological factor impacting the differences in the composition of the EAM microbiota. The three EAM groups had 52 common OTUs and 78.52% common sequences, among which the most abundant were Vibrio spp. and Photobacterium spp. The three types of EAM also had unique OTUs. The short EAMs had 238 unique OTUs and 48.61% unique sequences, mainly in the genera Shewanella and Cyanobacterium . The medium EAMs contained 130 unique OTUs and 4.36% unique sequences, mainly in the genera Pseudomonas and Bacillus . The long EAMs only had 27 unique OTUs and 4.13% unique sequences, mainly in the genus Marinobacter . Compared with short EAM, medium and long EAM had a lower proportion of autotrophic bacteria and higher proportion of potential pathogenic bacteria. It is suggested that EAMs with different phenotypes have different microbial compositions, and the ecological function of the EAM microbiota changes from autotrophic to pathogenic with an increase in algal length. As EAMs have expanded on coastal coral reefs worldwide, it is essential to comprehensively explore the community structure and ecological role of their microbial communities.

Efficient probabilistic back analysis of spatially varying soil parameters based on monitored displacements - Yibiao Liu; Chenchen Liu; Wenhui Xu; Simin Cai; Weizhong Ren (Arabian Journal of Geosciences, 2022)

Effects of Shear Stress and Salinity Stratification on Floc Size Distribution During the Dry Season in the Modaomen Estuary of the Pearl River - Jie Huang; Simin Wang; Xinran Li; Rongyao Xie; Jianxiong Sun; Benwei Shi; Feng Liu; Huayang Cai; Qingshu Yang; Zhaoyong Zheng (Frontiers in Marine Science, 2022)
The floc size distribution of fine cohesive sediments in estuaries varies spatiotemporally within assorted physical, chemical, and biological factors. However, the distribution of different floc fractions that are affected by shear stress and salinity stratification has not yet been thoroughly investigated. This study intends to clarify the floc size distribution within the influences of turbulent shear rate and salinity stratification, and the implications for the flocculation process during the dry season in the Modaomen Estuary of the Pearl River. The decomposition of multimodal floc size distributions (FSDs) indicates that the floc fractions were composed of macroflocs (Macro), microflocs (Micro), Flocculi, and primary particles (Pp). Macro generally existed among the upper and middle layers, but smaller flocs, i.e., Micro, Flocculi, and Pp, were mostly concentrated in the bottom layer. The results agreed that the flocculation and deflocculation processes were dominant in the upper and bottom layers, respectively. In response to strong turbulent shear rates, FSDs in the bottom layer skewed toward small sizes and had a dual-peak tendency with frequent floc exchanges between Pp and Micro, then being Pp-dominant but converting to Micro when turbulent shear rates decreased. With impeded vertical mixing by salinity stratification, the FSDs in the upper or middle layers skewed toward a larger particle size with single peaks and lack of exchange among different floc fractions, leading to Macro dominance with a larger volume concentration and median size. In addition, turbulence mixing dramatically interfered with the good mixing of floc fractions amidst the vertical water column, with a low-salinity condition greatly affecting the formation of Macro in the bottom layer within proper turbulent shear rates. This study explores the effects of shear stress and salinity stratification on the flocculation process in the Modaomen Estuary, which contributes to a better understanding of sediment movement in a complex estuarine environment.

Structural Characterization and Immunoenhancing Effects of a Polysaccharide from the Soft Coral Lobophytum sarcophytoides - Xueqin Cao; Qian Zhang; Yanglu Zhu; Siju Li; Ying Cai; Pei Li; Deliang Liu; Yun Leng; Simin Ye; Zengmei Xu; Hao Li; Baochun Shen; et al. (Marine Biotechnology, 2022)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

Disturbance-Mediated Changes in Coral Reef Habitat Provoke a Positive Feeding Response in a Major Coral Reef Detritivore, Ctenochaetus striatus - Xianzhi Lin; Simin Hu; Yong Liu; Li Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2021)
Coral reefs are undergoing global phase shifts from coral-dominated to algae-dominated stages. The negative effects of this substratum shift on the diversity and abundance of fish have been well documented, but the influence on fish feeding is less studied, which may limit a deeper understanding of trophic pathways in such a disturbed system. In this study, we investigated the feeding response of a numerically dominant fish species Ctenochaetus striatus to different substrate types, including hard coral, short algal turfs (SATs, <5 mm), and long algal turfs (LATs, >5 mm), on reefs in the South China Sea. The biomass of C. striatus showed an inverted U-shaped relationship with coral coverage and a significant positive correlation with SAT coverage ( p < 0.05), indicating that rising SAT coverage associated with moderate coral loss provoked a feeding response in C. striatus . Stomach contents of C. striatus , analyzed using high-throughput sequencing (HTS), were dominated by algal sequences (relative read abundance, RRA > 80.0%), including macroalgae, filamentous algae, and microalgae (e.g., Symbiodinium and Prorocentrum ). The sequence number and diversity of microalgae (mainly dinoflagellates) tended to be abundant (RRA 13.5–36.5%) with increased SAT cover, but brown algae sequences (RRA 17.2–57.8%) or green algae sequences (RRA > 50.7% except one site) dominated the stomach content DNA in reefs with high coral cover and high LAT or macroalgal cover, respectively. Considering the limited ability of C. striatus to remove mature algae, macroalgal DNA might be from algal debris. Our results indicate that C. striatus populations respond positively to conditions of moderate coral loss through increases in body condition identified as increased biomass. These responses are correlated to the expansion of SAT’s as coral cover declined, however, this relationship reverses if coral loss is high due to the succession of LAT’s over SAT’s and a corresponding decrease in the quality of food available. Our use of HTS has nevertheless identified the importance of detritivory in the flow of energy through reefs in the Anthropocene which are increasingly becoming depauperate in hard coral.

A search method for probabilistic critical slip surfaces with arbitrary shapes and its application in slope reliability analysis - Yibiao Liu; Weizhong Ren; Chenchen Liu; Guijun Fu; Wenhui Xu; Simin Cai (Natural Hazards, 2021)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

Dynamic relationship between meteorological conditions and air pollutants based on a mixed Copula model - Simin He; Zhiyao Li; Wenjie Wang; Mingxing Yu; Liangpo Liu; Md Nur Alam; Qian Gao; Tong Wang (International Journal of Climatology, 2021)
Many methods have been developed to verify the correlation between meteorological conditions and air pollutants; however, all have limitations that lead to biased or incomplete conclusions. Hence, improved methods are urgently required to describe this correlation comprehensively and accurately. In this study, we demonstrated the ability of the Copula function to apply time‐varying correlations between meteorological factors and atmospheric pollutants. A mixed Copula model was constructed using meteorological monitoring data for Beijing and Guangzhou from 2014 to 2019 to dynamically analyse the correlation characteristics and tail dependence between these factors. We then performed a correlation analysis for the data from the average, lower, and upper tails to obtain a more accurate and comprehensive correlation description. Dynamic analysis results demonstrated significant seasonal fluctuations between meteorological conditions and pollutants relationships. Moreover, the correlation coefficient variations differ according to their average and tail values. High humidity is more likely to be accompanied by increased NO 2 compared with average summer humidity. Our proposed model represents a novel application of the Copula function for determining the factors influencing air pollution. This model emphasizes the tail dependence between meteorological conditions and air pollutant concentrations and can be used to guide more targeted prevention and control strategies.

Mechanisms of high-frequency dinoflagellate blooms of Scrippsiella trochoidea in Daya Bay, South China Sea - Yuan Tian; Simin Hu; Xianzhi Lin; Hui Huang; Xingyu Song; Yan Yan; Xuedong Xie; Tao Li; Sheng Liu (Journal of Oceanology and Limnology, 2021)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Small Jellyfish as a Supplementary Autumnal Food Source for Juvenile Chaetognaths in Sanya Bay, China - Lingli Wang; Minglan Guo; Tao Li; Hui Huang; Sheng Liu; Simin Hu (Journal of Marine Science and Engineering, 2020)
Information on the in situ diet of juvenile chaetognaths is critical for understanding the population recruitment of chaetognaths and their functional roles in marine food web. In this study, a molecular method based on PCR amplification targeted on 18S rDNA was applied to investigate the diet composition of juvenile Flaccisagitta enflata collected in summer and autumn in Sanya Bay, China. Diverse diet species were detected in the gut contents of juvenile F. enflata, including copepods, small jellyfish, anthozoa, polychaetes, echinoderms, diatoms and dinoflagellates. The diet composition showed obvious differences between summer and autumn. Copepod, such as Temora turbinata, Canthocalanus pauper and Subeucalanus crassus, dominated the diet in summer, representing up to 61% of the total prey items. However, small jellyfish, mainly consisting of Bougainvillia fulva, Solmissus marshalli and Pleurobrachia globosa, was the main food group (72.9%) in autumn. Environmental parameters showed no significant difference between summer and autumn. The mean abundance of juvenile chaetognaths in autumn was about eight times higher than that in summer, while the abundance of potential food prey was similar in both seasons. Our results suggested that juveniles chaetognaths might consume small jellyfish as a supplementary food source under enhanced feeding competition in autumn.

Taxonomic revision of the Long-tailed Rosefinch Carpodacus sibiricus complex - Simin Liu; Chentao Wei; Paul J. Leader; Geoff J. Carey; Chenxi Jia; Yinan Fu; Per Alström; Yang Liu (Journal of Ornithology, 2020)

A continuous simulation of Holocene effective moisture change represented by variability of virtual lake level in East and Central Asia - Yu Li; Yuxin Zhang; Xinzhong Zhang; Wangting Ye; Lingmei Xu; Qin Han; Yichan Li; Hebin Liu; Simin Peng (Science China Earth Sciences, 2020)

Dietary separation between co-occurring copepods in a food-limited tropical coral reef of the Sanya Bay - Simin Hu; Tao Li; Sheng Liu; Hui Huang (Acta Oceanologica Sinica, 2020)

Isolation, structure elucidation, tyrosinase inhibitory, and antioxidant evaluation of the constituents from Angelica dahurica roots - Penghua Shu; Junping Li; Yingying Fei; Huiqing Zhu; Mengzhu Yu; Anqi Liu; Haoying Niu; Simin Zou; Xialan Wei; Zhiyu Ju; Zhihong Xu (Journal of Natural Medicines, 2020)

Flexible feeding patterns of copepod Centropages tenuiremis in fluctuating conditions: a possible survival strategy to cope with disturbance - Cuilian Xu; Simin Hu; Zhiling Guo; Tao Li; Hui Huang; Leo Lai Chan; Sheng Liu (Acta Oceanologica Sinica, 2020)

Correction to: Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

The protective microRNA-199a-5p-mediated unfolded protein response in hypoxic cardiomyocytes is regulated by STAT3 pathway - Yang Zhou; Bo Pang; Yingbin Xiao; Simin Zhou; Bin He; Fan Zhang; Wei Liu; Huali Peng; Peng Li (Journal of Physiology and Biochemistry, 2019)

Dibenzoylmethane Protects Against CCl4-Induced Acute Liver Injury by Activating Nrf2 via JNK, AMPK, and Calcium Signaling - Mingnan Cao; Huixia Wang; Limei Guo; Simin Yang; Chun Liu; Tin Oo Khor; Siwang Yu; Ah-Ng Kong (The AAPS Journal, 2017)

Temporal 18 O and deuterium variations in hydrologic components of a small watershed during a typhoon event - Simin Qu; Yifan Wang; Minmin Zhou; Han Liu; Peng Shi; Zhongbo Yu; Long Xiang (Isotopes in Environmental and Health Studies, 2017)

Prospective analysis of association between statins and pancreatic cancer risk in the Women’s Health Initiative - Michael S. Simon; Pinkal Desai; Robert Wallace; Chunyuan Wu; Barbara V. Howard; Lisa W. Martin; Nicolas Schlecht; Simin Liu; Allison Jay; Erin S. LeBlanc; Thomas Rohan; JoAnn Manson (Cancer Causes & Control, 2016)

Differences in oxygen-18 and deuterium content of throughfall and rainfall during different flood events in a small headwater watershed - Simin Qu; Minmin Zhou; Peng Shi; Han Liu; Weimin Bao; Xi Chen (Isotopes in Environmental and Health Studies, 2014)

Diabetes mellitus as a risk factor for gastrointestinal cancers among postmenopausal women - Juhua Luo; Rowan Chlebowski; Simin Liu; Katherine A. McGlynn; Niyati Parekh; Donna L. White; Karen L. Margolis (Cancer Causes & Control, 2013)

Morphology and mechanics of chondroid cells from human adipose-derived Stem cells detected by atomic force microscopy - Simin Luo; Qiping Shi; Zhengang Zha; Ping Yao; Hongsheng Lin; Ning Liu; Hao Wu; Hua Jin; Jiye Cai (Molecular and Cellular Biochemistry, 2012)

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)